2014
DOI: 10.1007/s00132-014-3053-0
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of local cortical defects in Charcot foot using microcomputed tomography

Abstract: By means of microCT we were able to visualize and quantify the extent of cortical porosity for the first time in high resolution. The data suggest that both cortical fractures and cortical porosity play an important role in the pathogenesis in cases of Charcot foot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Two severity grades are proposed according to the presence of cortical fracture and two stages (active/inactive) for inflammation signs. Senk et al showed microfractures in early stages of CN of the foot in micro-CT [12]. Scintigraphy and ultrasound have also been used for imaging but there is no classification or typical signs for CN defined [12].…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Two severity grades are proposed according to the presence of cortical fracture and two stages (active/inactive) for inflammation signs. Senk et al showed microfractures in early stages of CN of the foot in micro-CT [12]. Scintigraphy and ultrasound have also been used for imaging but there is no classification or typical signs for CN defined [12].…”
Section: Imagingmentioning
confidence: 99%
“…Senk et al showed microfractures in early stages of CN of the foot in micro-CT [12]. Scintigraphy and ultrasound have also been used for imaging but there is no classification or typical signs for CN defined [12]. Using a PET-CT scan to find early inflammation in CN of the foot has been proposed by Ruttolo et al [13].…”
Section: Imagingmentioning
confidence: 99%